Optical characteristics of ZnSxSe1−x thin films prepared by electron beam evaporation - Abo-Hassan, Khedr M.M.; Muhamad, Muhamad Rasat; Radhakrishna, S. (Elsevier, 2005)
The optical transmission measurements are used to determine various optical constants and properties of ZnSxSe1-x thin films prepared by electron beam evaporation onto glass substrates at 60 °C. The dispersion of the complex refractive index, the complex dielectric function and the absorption coefficient is studied in the transparent region of the spectrum and compared with the theoretical results calculated based on the model dielectric function. The fundamental optical energy gap is estimated by fitting the absorption coefficient data in the high absorption region to the direct transition expression. The variation of the energy gap with the composition in the film is investigated and compared with the results reported previously by other workers. The shift in the energy gap caused by the uniaxial stress inside the film and the grain size effect is estimated. © 2005 Elsevier B.V. All rights reserved.